PENGEMBANGAN MEDIA KOMIK DIGITAL CERITA FIKSI UNTUK MENINGKATKAN KETERAMPILAN MENULIS SISWA KELAS IV SEKOLAH DASAR - Amelia Putri Kristiani; Bramianto Setiawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The development of science and technology is developing rapidly. This change in development affects all aspects of life, including the aspect of education. One example of the negative influence is related to the character of students who tend to be influenced by attitudes. Narrative writing skills are language skills that must be mastered by students so that writing skills are considered important to be taught in every elementary school, so that students are able to come up with ideas and ideas. This research was conducted in grade IV of elementary school located in Sukadami Cikarang Selatan, Bekasi Regency, West Java. The type of research used is research and development (Research and Development) with the ADDIE development model, research and development produces digital comic media products for fictional stories to improve students' writing skills. Digital Comics Fiction Stories were declared very valid after the media was revised with an average of 98%. Based on the results of the assessment of the questionnaire response